India’s Incipient Comparative Advantage and Trade Specialization in Pharmaceutical Sector in Comparison to ASEAN - Oberoi, Sumit; Kansra, Pooja (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Today the whole world is looking towards the rising role of Asian nations in the world trade. Amid 48 Asian nations, India’s pharmaceutical segment observed a crucial restructuring in mounting income and occupational opportunities. Aim/ Objectives: Therefore, the present study aims at measuring comparative advantage and trade specialization between India and selected ASEAN economies at harmonized standard 4-digit level of product categorization. Materials and Methods: Statistical indexes meticulously assess the secondary data by performing revealed comparative advantage (RCA) index and Lafay index. Results: Outcomes lucidly elucidate that India embraces comparative advantage and trade-specialization for pharmaceutical sectors viz. ‘Bulk Medicines’, ‘Inputs Specific to Pharmaceutical Industry’ and ‘Medical technology equipment”. Conclusion: Thus, the results advocates that industrial progressions, technical innovation, product sophistication and commodity diversification in pharmaceutical sector is a pre-requisite for India to clinch trade superiority.
Keywords: Pharmaceutical Sector; India; ASEAN; Trade Specialization; Comparative; Advantage